2020
DOI: 10.1002/ange.202006921
|View full text |Cite
|
Sign up to set email alerts
|

Methanol‐Assisted Autocatalysis in Catalytic Methanol Synthesis

Abstract: Catalytic methanol synthesis is one of the major processes in the chemical industry and may grow in importance, as methanol produced from CO2 and sustainably derived H2 are envisioned to play an important role as energy carriers in a future low‐CO2‐emission society. However, despite the widespread use, the reaction mechanism and the nature of the active sites are not fully understood. Here we report that methanol synthesis at commercially applied conditions using the industrial Cu/ZnO/Al2O3 catalyst is dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Syngas to methanol synthesis takes place over copper oxide, zinc oxide, or chromium oxide‐based catalysts. Although the mentioned technology is around one century old, the catalytic pathways of the used reaction have been understood only in recent years (Laudenschleger et al, 2020; Thrane et al, 2020). Methanol synthesis catalysts also are sensitive to syngas pollutants, especially sulfur‐organic and chlorine‐organic compounds (Quinn et al, 2004).…”
Section: Thermal Transformation Character and Thermochemical Treatment Of Wastesmentioning
confidence: 99%
“…Syngas to methanol synthesis takes place over copper oxide, zinc oxide, or chromium oxide‐based catalysts. Although the mentioned technology is around one century old, the catalytic pathways of the used reaction have been understood only in recent years (Laudenschleger et al, 2020; Thrane et al, 2020). Methanol synthesis catalysts also are sensitive to syngas pollutants, especially sulfur‐organic and chlorine‐organic compounds (Quinn et al, 2004).…”
Section: Thermal Transformation Character and Thermochemical Treatment Of Wastesmentioning
confidence: 99%
“…10,11 Recently, the same group managed to confirm their findings also in the gas phase by continuously dosing methanol as promoter at low temperatures. 12 In addition, also the Christensen group 13 reported on the autocatalytic influence of methanol on high-conversion gas-phase methanol synthesis. By lowering the space velocity causing high conversion over Cu/ZnO/Al 2 O 3 , it was found that the rate of methanol synthesis increased exponentially in agreement with other studies reporting on an increased methanol formation rate with increasing conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, temperatureprogrammed reduction (TPR) experiments predicted methyl formate to be a probable intermediate of the assumed pathway. According to the Tsubaki group 10,11 and Christensen group 13 methyl formate ester is formed from methanol and formate (HCOO*) (eqn (1)):…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations